Adaptive Under-Frequency Load Shedding Control Strategy of Power Systems With Wind Turbines and UHVDC Participating in Frequency Regulation - Wu, Xingyang; Xue, Feng; Dai, Jianfeng; Tang, Yi (Frontiers in Energy Research, 2022)
Represented by wind turbines and ultra high-voltage DC (UHVDC), the power-electronic interfaced power sources participate in fast frequency control, which has a significant impact on the power system frequency. However, the conventional under-frequency load shedding (UFLS) scheme doesn’t take into account the impact above, resulting in unreasonable load shedding after a large loss of generation. To this end, this article proposes an adaptive UFLS control strategy of power systems with wind turbines and UHVDC participating in frequency regulation. Firstly, based on the virtual inertia control model and the primary frequency control model of wind turbines and UHVDC, the study establishes the simplified frequency response model of the power system considering the participation of wind turbines and UHVDC in frequency regulation. Furthermore, the impact of the active power response characteristics of wind turbines and UHVDC participating in frequency regulation on the magnitude of the active power deficiency is comprehensively analyzed. Thus the precise estimation of the magnitude of the power deficiency can be achieved, which provides technical guidance for multi-stage UFLS. Finally, simulation results demonstrate that the proposed UFLS strategy is capable of reflecting the power system frequency more objectively after a large loss of generation event. In addition, the proposed UFLS strategy outperforms the conventional UFLS strategy in terms of shedding less amount of load when the same desired effect of frequency recovery is achieved.